2007
DOI: 10.1128/aac.00264-07
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Antimalarial Activities of Six Pairs of 1,2,4,5-Tetraoxanes (Peroxide Dimers) and 1,2,4,5,7,8-Hexaoxonanes (Peroxide Trimers)

Abstract: Six tetraoxanes had 50% inhibitory concentrations in the range of 10 to 100 ng/ml against Plasmodium falciparum, whereas the corresponding hexaoxonanes had minimal antimalarial activity. The lack of ironmediated reactivity of the hexaoxonanes may explain their low activity compared to the tetraoxanes, the latter of which are able to undergo iron(II)-mediated activation.The antimalarial artemisinin (qinghaosu) contains a pharmacophoric peroxide bond within its 1,2,4-trioxane heterocycle. The complex structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…It is important to mention here that most common side product of tetraoxane synthesis is 1,2,4,5,7,8-hexaoxonanes; although it contains peroxide bond, this class of compounds shows very poor antimalarial activity. 90 In order to understand the mechanistic insight of the activity difference, reactivity of tetraoxanes and hexaoxonanes with Fe(II) was investigated. 90 Tetraoxane underwent complete degradation in the presence of FeSO 4 , while hexaoxonanes did not show any reactivity with FeSO 4 .…”
Section: Oacmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to mention here that most common side product of tetraoxane synthesis is 1,2,4,5,7,8-hexaoxonanes; although it contains peroxide bond, this class of compounds shows very poor antimalarial activity. 90 In order to understand the mechanistic insight of the activity difference, reactivity of tetraoxanes and hexaoxonanes with Fe(II) was investigated. 90 Tetraoxane underwent complete degradation in the presence of FeSO 4 , while hexaoxonanes did not show any reactivity with FeSO 4 .…”
Section: Oacmentioning
confidence: 99%
“…90 In order to understand the mechanistic insight of the activity difference, reactivity of tetraoxanes and hexaoxonanes with Fe(II) was investigated. 90 Tetraoxane underwent complete degradation in the presence of FeSO 4 , while hexaoxonanes did not show any reactivity with FeSO 4 . Lack of iron-mediated reactivity of hexaoxonanes may be responsible for low antimalarial activity of hexaoxonanes.…”
Section: Oacmentioning
confidence: 99%
See 1 more Smart Citation
“…This study uses a substantially improved level of theory to confirm previous assertions that steric interactions around the peroxide bond influence the interaction with iron, and therefore determine antimalarial activity. The general relationship between peroxide bond exposure, ironmediated reactivity and antimalarial activity has also been shown for other trioxolanes [10], trioxanes [9], trioxepanes [32], tetraoxanes and hexaoxanes [33]. It therefore appears important to limit the steric hindrance around the peroxide bond when designing new synthetic peroxide antimalarials; however it is possible that excessive reactivity with iron may lead to increased drug clearance in vivo [10,13].…”
Section: Discussionmentioning
confidence: 88%
“…Free radicals or metallic ions in solution can interact with the O O bond, accelerating their decomposition reactions. For example, the antimalarial activities of some 1,2,4,5-tetraoxacyclohexanes and 1,2,4,5,7,8-hexaoxacyclononanes structurally related with I and II have been studied and compared with the antimalarial activity of the artemisinin (qinghaosu) extracted from the Chinese Artemisia plant [20], which contains a pharmacophoric peroxide bond within its 1,2,4-trioxacyclohexane cycle. It was demonstrated that the antimalarial specificity of artemisinin is that its peroxidic bond undergoes reductive activation by heme released by parasite hemoglobin digestion.…”
Section: Catalytic Behaviormentioning
confidence: 99%